New Collembola occurrence records from the western Antarctic Peninsula - Yurii Protsenko; Oleksandra Protsenko; Pavlo Kovalenko; Ivan Parnikoza; Anton Puhovkin; Leonid Svetlichny; Peter Convey; Iryna Kozeretska (Ukrainian Antarctic Journal, 2025)
In the light of the considerable global climatic changes observed over recent decades, and particularly their magnification in the western Antarctic Peninsula (WAP) region (maritime Antarctic), it is important to document in detail the biodiversity of this region to provide a baseline for assessing potential future shifts in species distribution ranges. The aim of this study was to document the species diversity of springtails (Collembola) collected during the Antarctic summer season (December 2023 to March 2024) from various locations in the coastal regions of the WAP. A total of 141 invertebrate samples were collected and analysed from different types of vegetated substrates, predominantly mosses, and from the nesting materials of the seabirds Stercorarius maccormicki and Larus dominicanus. Samples were obtained from 35 locations within four sub-regions of the WAP, including the South Shetland Islands, Graham Coast, Biscoe Islands and Adelaide Island and its neighbouring islands. For 20 of these surveyed locations, Collembola diversity was recorded for the first time and, for a further three locations, new records were obtained supplementing those in the existing literature. A total of 9 143 Collembola specimens were identified, representing three species: Cryptopygus antarcticus, Folsomotoma octooculata and Friesea antarctica, all of which are native to the studied region. Two of these species were identified in bird nest material, with Fo. octooculata being absent. Although all three species were present in many of the samples obtained, C. antarcticus was generally the most abundant, both in samples from vegetated substrates and in the nesting material of both bird species, accounting for nearly 90% of all collected specimens. This likely indicates a high degree of ecological plasticity in C. antarcticus, which may facilitate its persistence in the harsh environmental conditions of Antarctica amid ongoing climate change.